Analysis of the regression of transient neurological symptoms in newborns during physiological childbirth - A. V. Petrova; E. A. Morozova; A. A. Khasanov (Русский журнал детской неврологии)
The authors of the article substantiate the high significance and prognostic value of transient neurological symptoms in newborns. The study showed a greater variety and a lower rate of symptoms regression in the part of neurological disorders during physiological childbirth in the second position of the fetus. There are data on a higher frequency of some variants of torticollis in the second position of the fetus, cephalohematoma during childbirth in the second position was also significantly more often found. The findings are important for the prevention of neurological disorders and revision of some aspects of obstetric tactics.